New Diagnostic Real-Time PCR for Specific Detection of Mycoplasma hominis DNA - Andres Pascual; Katia Jaton; Béatrice Ninet; Jacques Bille; Gilbert Greub (International Journal of Microbiology)
Mycoplasma hominis is a fastidious micro-organism causing genital and extragenital infections. We developed a specific real-time PCR that exhibits high sensitivity and low intrarun and interrun variabilities. When applied to clinical samples, this quantitative PCR allowed to confirm the role of M. hominis in three patients with severe extragenital infections.